1981
DOI: 10.1002/dvg.1020020402
|View full text |Cite
|
Sign up to set email alerts
|

Organization of mitochondrial DNA in normal and texas male sterile cytoplasms of maize

Abstract: Recombinant DNA and hybridization techniques have been used to compare the organization of mitochondrial DNA (mtDNA) from normal (N) and Texas male sterile (T) cytoplasms of maize. Bum H1 restriction fragments of normal mtDNA were cloned and used in molecular hybridizations against Southern blots of Bum H I digested N and T mtDNA. Fifteen of the 35 fragments were conserved in both N and T as indicated by hybridization to comigrating bands in their restriction patterns. Only three fragments produced autoradiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1983
1983
1986
1986

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 38 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…The homologies were identifed by hybridizing a nick-translated 2.3-kb Hind111 restriction fragment from an internal region of S-1 with Southern blots containing BamHI digests of mtDNA and ctDNA from normal and cytoplasmic male-sterile (cms) lines of maize (Figure 2A). The variability of hybridization to the N, cms-S, and cms-T mtDNAs reflects differences in the relative stoichiometry and extent of the S-1 homologous sequences in the three mitochondrial genotypes (LEVINGS et SPRUILL, LEVINGS and SEDEROFF 1981;. The probe hybridizes to a 6.9-kb fragment in normal mtDNA that represents an integrated form of R-1 (LEVINGS et al.…”
Section: Resultsmentioning
confidence: 99%
“…The homologies were identifed by hybridizing a nick-translated 2.3-kb Hind111 restriction fragment from an internal region of S-1 with Southern blots containing BamHI digests of mtDNA and ctDNA from normal and cytoplasmic male-sterile (cms) lines of maize (Figure 2A). The variability of hybridization to the N, cms-S, and cms-T mtDNAs reflects differences in the relative stoichiometry and extent of the S-1 homologous sequences in the three mitochondrial genotypes (LEVINGS et SPRUILL, LEVINGS and SEDEROFF 1981;. The probe hybridizes to a 6.9-kb fragment in normal mtDNA that represents an integrated form of R-1 (LEVINGS et al.…”
Section: Resultsmentioning
confidence: 99%
“…Hybridization studies with cemigrating fragments indicated that extensive divergence of sequence organization distinguished cms-T from N cytoplasm (Spruill et al, 1981).…”
Section: Information To Usersmentioning
confidence: 99%
“…It has been shown that nuclear background can influence the content and relative proportions of S-I and S-2 (Laughnan et al, 1981). Several studies have shown that mtDNA sequences from normal (fertile) and male-sterile cytoplasms share homology with S-1 and S-2 sequences (Spruill et al, 1980(Spruill et al, , 1981Lonsdale et al, 1981). Moreover, sequences homologous to S-1 are reported to occur in the maize nuclear genome .…”
Section: Introductionmentioning
confidence: 99%